A new species of Ultratenuipalpus (Acari: Tenuipalpidae) from Cook Islands, with a key to the known species - Xu, Yun; Fan, Qing-Hai; Zhang, Zhi-Qiang (Zootaxa, 2013)
The genus Ultratenuipalpus (Acariformes: Tenuipalpidae) was represented by 24 species prior to this study. In this paper, we describe and illustrate Ultratenuipalpus avarua sp. nov, from Cocos sp. (Arecaceae) in Avarua, Rarotonga, the Cook Islands. A key to the world species of Ultratenuipalpus is provided.